Wilfred Owen's Anger Over the Loss of Young Soldiers' Lives in the Poem "Anthem for Doomed Youth" - Amal M. A. Ibrahim Ibrahim (Taez University, 2024)
The study highlights Wilfred Owen's anger over the Loss of Young Soldiers' Lives in the Poem "Anthem for Doomed Youth". The objectives of the study are to show the anger of Wilfred Owen over the loss of young soldiers' lives, to show the physical and psychological state of the soldiers after the war, and to highlight the language of war poetry emphasizes some topics, such as suffering and death, violence, terror by the army, and hopelessness presented by the poet. The paper used a descriptive and analytical methodology to comprehend Owen's message about his refusal to funeral young soldiers in war. According to the study's conclusion, greater consideration must be given to those who defend their country, and their sacrifice when they pass away in war has to be recognized and appreciated. Consideration must be taken of the psychological state of those soldiers.